The world in the head - Cummins, Robert (Oxford ; New York : Oxford University Press, 2010)
The World in the Head collects the best of Robert Cummins' papers on mental representation and psychological explanation. Running through these papers are a pair of themes: that explaining the mind requires functional analysis, not subsumption under "psychological laws", and that the propositional attitudes--belief, desire, intention--and their interactions, while real, are not the key to understanding the mind at a fundamental level. Taking these ideas seriously puts considerable strain on standard conceptions of rationality and reasoning, on truth-conditional semantics, and on our interpretation of experimental evidence concerning cognitive development, learning and the evolution of mental traits and processes. The temptation to read the structure of mental states and their interactions off the structure of human language is powerful and seductive, but has created a widening gap between what most philosophers and social scientists take for granted about the mind, and the framework we need to make sense what an accelerating biology and neuroscience are telling us about brains. The challenge for the philosophy of mind is to devise a framework that accommodates these developments. This is the underlying motivation for the papers in this collection.
1.What is it like to be a computer? -- 2.The LOT of the casual theory of mental content -- 3.Systematicity -- 4.Systemacity and the cognition of stuctured domains /Robert Cummins, Jim Blackmon, David Byrd, Pierre Poirier, Martin Roth, and Georg Scwarz -- 5.M ethodological reflections on belief -- 6.Inexplicit information -- 7.Representation and indication / Robert Cummins and Pierre Poirier -- 8.Representation and unexploited content / Robert Cummins, Jim Blackmon, David Byrd, Alexa Lee, and Martin Roth -- 9.Haugeland on representation and intentionality -- 10.Truth and meaning --11.Meaning and content in cognitive science / Robert Cummins and Martin Roth -- 12.Representational specialization : the synthetic a priori revisited -- 13.Biological preparedness and evolutionary explanation / Robert Cummins and Denise Dellarosa Cummins -- 14.Cognitive evolutionary psychology without representation nativism / Robert Cummins, Denise Dellarosa Cummins and Pierre Poirier -- 15.Connectionism and the rationale constraint on cognitive explanation -- 16.'How does it work?' vs. 'What are the laws?' : two conceptions of psychological explanation.
Na kraju svakog poglavlja bibliografija..
Str. [311]-320: Bibliografija.
Kazalo